Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar IPA Kelas V MIM Plus Suwaru - Aziz, Isfah Abidal; Amelia, Rizki (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The success of the learning process is the main target in implementing learning. However, student learning outcomes in class V MI Muhammadiyah Plus Suwaru Bandung are not optimal. Thus, the Problem Based Learning learning model is applied as an alternative solution. This research is classroom action research using the Kemmis Mc Taggart model. Classroom Action Research procedures consist of planning, implementation, observation, reflection. Data collection techniques consist of interviews, observations, tests, field notes and documentation. Data analysis techniques use percentage techniques by comparing the scores obtained by students with the ideal maximum score. Learning by applying the Problem Based Learning learning model is declared successful if there is an increase in student learning outcomes of at least 75% of the total number of students achieving a complete learning score, namely above 70. In cycle I the learning outcomes achieved by students have not reached completeness because the percentage of completeness is only 73 % (not yet completed), while in cycle II there was a slight increase, this increase was with a percentage of learning completeness of 77% in the category (not yet completed). while in cycle III there was a significant increase, this increase was with a learning completeness percentage of 93% in the (complete) category. This shows that science learning using the problem based learning model can improve student learning outcomes